Differences in Older Patients' Attitudes Toward Deprescribing at Contextual and Individual Level - Oktora, Monika Pury; Edwina, Angela Elma; Denig, Petra (Frontiers in Public Health, 2022)
Background:Deprescribing requires patients’ involvement and taking patients’ attitudes towards deprescribing into account. To understand the observed variation in these attitudes, the influence of contextual-level factors, such as country or healthcare setting, should be taken into account.Methods:We conducted a systematic review of studies using the revised Patients' Attitudes Towards Deprescribing(rPATD) questionnaire among older adults. We searched articles in Medline and Embase up to 30 June 2021.PRISMA guideline was used for the search process and reporting. We summarized the outcomes from the rPATD and compared attitudes at study population level between high or low-middle-income countries,global regions,and healthcare settings using ANOVA testing. Correlations of the rPATD outcomes with the mean age of the study populations were tested. Associations with the rPATD outcomes at individual patient level were tested.Results:Sixteen articles were included. Percentages of patients willing to stop medication were significantly lower in low-middle-income countries(<70% in Nepal and Malaysia) compared to high-income countries (>85% in USA,Australia,European countries). No significant differences were observed when results were compared by global region or by healthcare setting but a high willingness (>95%) was seen in the two studies conducted in an inpatient population. A higher mean age at study level was associated with a higher willingness to stop medication. At individual level, associations between patient characteristics, including demographics and education, and attitudes towards deprescribing showed inconsistent results.Conclusion:Findings about attitudes towards deprescribing are influenced by contextual factors.Future research should pay more attention to the influence of the healthcare system and setting as well as the culture on patients’ attitudes.